Strategi Penyebaran Konten Digital TVRI Bali dalam Meningkatkan Visibilitas Berita Lokal - Ni Putu Rika Anggarani; Kadek Devi Kalfika Anggria Wardani; Putu Suparna; Sahri Aflah Ramadiansyah (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study examines the digital communication strategy through the distribution of TVRI Bali's digital content in increasing the visibility of local news on social media as a form of broadcast media adaptation in the era of media convergence. The study used a qualitative approach, data collection was conducted through observation, interviews, and document studies of TVRI Bali's media content division, divisions that assist with content distribution, and TVRI Bali's social media audience. The results showed that the New Media Content Division helped optimize the use of social media by designing, managing, and distributing content on social media and conducting audience interest analysis to determine the right posting time. Other strategies were carried out by using attractive visuals, and utilizing content distribution formats by selecting keywords, hooks, and SEO. In addition, citizen journalism activities, inter-media mentions, and contributors from each region in Bali accelerated uploads on social media. Through targeted content design and strengthening collaboration between divisions and external parties, TVRI Bali's New Media Content Division was able to produce diverse content and maintain consistent uploads according to the results of audience interest analysis, so that the formulated strategy could become a plan and reference in increasing news visibility on social media platforms.